Augusto Rodrigues Duarte: a clown among verses, newspapers and jokes in nineteenth-century Brazil (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
Among the vast circus production in Brazil in the 19th century, the performance of clowns and, therefore, comicity had a strong presence in the shows. In this sense, this article aims to analyze part of the performance of the clown Augusto Rodrigues Duarte, accessing the multiplicity of his presentations and the mixture of expressions and techniques that he mobilized in his artistic achievements in the diverse and complex scenario of circus comedy of the period. To this end, a survey and cross-referencing of different sources was carried out, mainly 19th century newspapers that were consulted in the Hemeroteca Digital of the National Library (RJ). Thus, this study is dedicated to the professional production of Augusto R. Duarte, an artist little known by the bibliography, and to disseminate and expand the understanding of the production of comicity in the 19th century and its artists, in addition to clowns of the time already contemplated with various studies and publications.
Keywords: Clown; Comicity; Circus; History